ГОСУДАРСТВЕННАЯ ОБРАЗОВАТЕЛЬНАЯ ПОЛИТИКА ИНТЕЛЛЕКТУАЛЬНОГО И ТВОРЧЕСКОГО РАЗВИТИЯ НОВОГО ПОКОЛЕНИЯ УЧАЩИХСЯ (Scientific journal of the Fergana State University, 2023)
The article deals with the extracurricular study of history and culture of England and the formation of high spirituality, culture and creative thinking of students.